FACTORS AFFECTING LIQUIDITY COVERAGE RATIO (LCR) AS IMPLEMENTATION OF BASEL III IN THE BANKING SECTOR - Sitepu, Risna Waty (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aims to examine and analyze the effect of Return On Assets (ROA), Capital Adequacy Ratio (CAR), Operational Costs to Operating Income (OCOI), Non Performing Loans (NPL), Third Party Funds (TPF) and bank size on Liquidity Coverage Ratio (LCR) in the banking sector. The population of this study are banks that are required by the Financial Services Authority to calculate and publish LCR reports on a quarterly basis in 2017-2018 which includes banks BOOK 4, BOOK 3 and foreign banks. The population of this research is 33 banks. The sample selection using purposive sampling method with the selected sample is 23 banks. Processing data using panel data regression statistical test methods. The results of this study indicate ROA, CAR, OCOI, NPL, TPF and bank size simultaneously affect LCR. NPL partially has a negative and significant effect on LCR. ROA, OCOI, TPF and bank size variables have positive but not significant effect on LCR. CAR variable has a negative but not significant effect on LCR.